Analisis Wacana Kritis 708 Komentar Warganet pada YouTube CNN Indonesia tentang Pidato Presiden Peresmian SPPG - Roni Sianturi; Merry Lapasau; Andrianus Adi; Ahmad Farhan; Efimery Afriya; Dewi Puspitasari (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2026)
The development of digital media has transformed the patterns of public communication in expressing opinions toward the various issues emerging in the public sphere. The presence of comment sections on the media platforms enables netizens to express their views, criticisms, support, and evaluations through diverse language usage. That phenomenon makes the digital space as a crucial component in the formation of modern public communication. Previous studies have examined language use on social media, such as linguistic style, speech acts, and the forms of netizen interaction in digital communication. However, prior research has tended to focus on general linguistic aspects and has not extensively examined the discourse trends emerging in public interactions within online media comment sections. Therefore, this study was conducted to describe language use and the discourse trends that emerge in netizens’ communication on digital media. This study is expected to contribute to the development of linguistic studiìes, particularly in undìerstanding thìe dynamics of public communication in thìe digital agìe. Additionally, this study is also ìexpìectìed to sìervìe as a rìefìerìencìe for futurìe rìesìearch rìelatìed to languagìe, digital mìedia, and public communication.